The biochemical properties of the two Arabidopsis thaliana isochorismate synthases - Macaulay, Keith M. (Biochem J, 2017)
The important plant hormone salicylic acid (SA; 2-hydroxybenzoic acid) regulates several key plant responses including, most notably, defence against pathogens. A key enzyme for SA biosynthesis is isochorismate synthase (ICS), which converts chorismate into isochorismate, and for which there are two genes in Arabidopsis thaliana. One (AtICS1) has been shown to be required for increased SA biosynthesis in response to pathogens and its expression can be stimulated throughout the leaf by virus infection and exogenous SA. The other (AtICS2) appears to be expressed constitutively, predominantly in the plant vasculature. Here, we characterise the enzymatic activity of both isozymes expressed as hexahistidine fusion proteins in Escherichia coli. We show for the first time that recombinant AtICS2 is enzymatically active. Both isozymes are Mg(2+)-dependent with similar temperature optima (ca. 33°C) and similar K(m) values for chorismate of 34.3 ± 3.7 and 28.8 ± 6.9 µM for ICS1 and ICS2, respectively, but reaction rates were greater for ICS1 than for ICS2, with respective values for V(max) of 63.5 ± 2.4 and 28.3 ± 2.0 nM s(−1) and for k(cat) of 38.1 ± 1.5 and 17.0 ± 1.2 min(−1). However, neither enzyme displayed isochorismate pyruvate lyase (IPL) activity, which would enable these proteins to act as bifunctional SA synthases, i.e. to convert chorismate into SA. These results show that although Arabidopsis has two functional ICS enzymes, it must possess one or more IPL enzymes to complete biosynthesis of SA starting from chorismate.